Fusarium longipes-a mycoparasite of Sclerospora graminicola on pearl millet - S.D. SINGH, S.S. NAVI and (Indian Phytopathology, 2002)
A mycoparasite, Fusarium longipes Wollenw. and Reinking, parasitizing Sclerospora graminicola, that causes downy mildew of pearl millet is reported. The mycoparasite attacks only downy mildew-infected areas of the leaves. The rnycoparasite produces brownish, spots with variable sizes and may cover the entire infected leaf under humid conditions resulting in the complete inhibition of sporangial production. Such plants are killed immaturely. Attempts to selectively control the mycoparasite by the use of fungicide or to identify genotypes which can support S. graminicola but not F. longipes have been unsuccessful.